AETHIOPS - AETHIOPICA - AETHIOPS: 1922 - 1938 Sylvain Grébaut à la tâche - Tubiana, Joseph (Aethiopica, 1998)
Sylvain Grébaut (1881–1955) devoted his life to Ethiopian studies. He collected Ethiopic Mss. for the Vatican Library, taught Ethiopic at the Catholic University of Paris, described a considerable number of Mss., edited and translated religious texts, and accumulated day by day a variety of lexical information, in order to complete Dillmann’s Lexicon. This made him realise the usefulness of a scholarly journal to preserve all this knowledge. He attained only partial success, with great effort and labour. This article contains parts of the gadl of Sylvain Grébaut, which reminds one of the story of S. Yared and the caterpillar.